Clara cell adhesion and migration to extracellular matrix - Atkinson, Jeffrey J (BioMed Central, 2008)
BACKGROUND: Clara cells are the epithelial progenitor cell of the small airways, a location known to be important in many lung disorders. Although migration of alveolar type II and bronchiolar ciliated epithelial cells has been examined, the migratory response of Clara cells has received little attention. METHODS: Using a modification of existing procedures for Clara cell isolation, we examined mouse Clara cells and a mouse Clara-like cell line (C22) for adhesion to and migration toward matrix substrate gradients, to establish the nature and integrin dependence of migration in Clara cells. RESULTS: We observed that Clara cells adhere preferentially to fibronectin (Fn) and type I collagen (Col I) similar to previous reports. Migration of Clara cells can be directed by a fixed gradient of matrix substrates (haptotaxis). Migration of the C22 cell line was similar to the Clara cells so integrin dependence of migration was evaluated with this cell line. As determined by competition with an RGD containing-peptide, migration of C22 cells toward Fn and laminin (Lm) 511 (formerly laminin 10) was significantly RGD integrin dependent, but migration toward Col I was RGD integrin independent, suggesting that Clara cells utilize different receptors for these different matrices. CONCLUSION: Thus, Clara cells resemble alveolar type II and bronchiolar ciliated epithelial cells by showing integrin mediated pro-migratory changes to extracellular matrix components that are present in tissues after injury.